Is age-related myelinodegenerative change an initial risk factor of neurodegenerative diseases? - Shuangchan Wu; Jun Chen (Neural Regeneration Research)
Myelination, the continuous ensheathment of neuronal axons, is a lifelong process in the nervous system that is essential for the precise, temporospatial conduction of action potentials between neurons. Myelin also provides intercellular metabolic support to axons. Even minor disruptions in the integrity of myelin can impair neural performance and increase susceptibility to neurological diseases. In fact, myelin degeneration is a well-known neuropathological condition that is associated with normal aging and several neurodegenerative diseases, including multiple sclerosis and Alzheimer’s disease. In the central nervous system, compact myelin sheaths are formed by fully mature oligodendrocytes. However, the entire oligodendrocyte lineage is susceptible to changes in the biological microenvironment and other risk factors that arise as the brain ages. In addition to their well-known role in action potential propagation, oligodendrocytes also provide intercellular metabolic support to axons by transferring energy metabolites and delivering exosomes. Therefore, myelin degeneration in the aging central nervous system is a significant contributor to the development of neurodegenerative diseases. Interventions that mitigate age-related myelin degeneration can improve neurological function in aging individuals. In this review, we investigate the changes in myelin that are associated with aging and their underlying mechanisms. We also discuss recent advances in understanding how myelin degeneration in the aging brain contributes to neurodegenerative diseases and explore the factors that can prevent, slow down, or even reverse age-related myelin degeneration. Future research will enhance our understanding of how reducing age-related myelin degeneration can be used as a therapeutic target for delaying or preventing neurodegenerative diseases.